KAJIAN KOMPETENSI ANGGOTA DEWAN PERWAKILAN RAKYAT DAERAH KABUPATEN - KOTA SUKABUMI, PROVINSI JAWA BARAT - Wahyuningsih, Tiesnawati; Krida Sakti, Sri Wahyu (LPPM Universitas Terbuka, 2010)
The overall picture of the regional legislative members competency both in the regency or in the city of Sukabumi to do their function in legislatory, budgetary, and supervisory showed very critical condition to be well fixed in immediate constructs. The intellectual capacity as well as the standard behavior and technical skills to produce local regulations are still pretty weak. Generally speaking the local legislative members knowledgebility about their three main tasks and functions which are to do with local economic development, local tax and retribution, also the creation of condusive business entrepreneurship climate, all of them have lommed to be very sluggish. More substancially, the mastery of basic competencies to do with the settlement of local budgeting and revenue planning are still being handycap. This research discusses the profile of those of three main synergetic competences of local legislative members in Sukabumi, both the city and the regency. The three main synergetic competences of that of local legislative members cover local-law-legislation, local-development-supervision, and local-budgeting. More specifically, those three main variables of legislative competence were also analyzed by using five parameters of competence which are technical, managerial, strategical, social, and ethical.